Chicago Fire: Season Twelve Season twelve - Brandt, Michael, 1968-; Wolf, Dick; Kinney, Taylor, 1981-; Walker, Eamonn; Eigenberg, David, 1964-; Universal Pictures (Firm) (Universal City, CA : Universal, 2024)
Chicago Fire returns hotter than ever with an all-new season chronicling the professional and personal lives of the firefighters, rescue squad and paramedics of Chicago's Firehouse 51. More like family than co-workers, the brave men and women of Firehouse 51 are committed to putting it all on the line for each other day after day to save and protect the citizens of Chicago. Balancing life-or-death stakes with complex interpersonal relationships, the Firehouse 51 family gets back to work in Season 12 of the exhilarating drama from Emmy Award winning executive producer Dick Wolf.
Title from web page.
Originally broadcast as single episodes of a television program in 2024.
Wide screen (1.78:1).
Taylor Kinney, Eamonn Walker, David Eigenberg.
Rating: Not rated.
English subtitles for the deaf and hard-of-hearing (SDH).
Keywords: Fire fighters -- Illinois -- Chicago -- Drama; Emergency medical technicians -- Illinois -- Chicago -- Drama; Chicago (Ill.) -- Drama; Action and adventure television programs; Television melodramas; Fiction television programs; Television series; Video recordings for the hearing impaired